Orientasi Kebijakan Pemberantasan Korupsi Negara Asia Menurut Ranking Corruption Perception Index: The Orientation of Policy Corruption Eradication in Asian Countries According to Corruption Perception Index Rank - Okparizan Okparizan; Lesmana Rian Andhika (Pusjar SKPP Lembaga Administrasi Negara, 2020)
This study discusses the effort against corruption eradication in Asian countries which is a manifestation from the corruption itself. To that goal, this study adopted a literature review to explore ways to corruption eradication (secondary data). Meanwhile from the literature review, the analysis provided information that corruption eradicating was more directed at preventive measures through education in early childhood at the elementary school programs as an investment in future integrity. The citizen participation, institutions cooperation, good governance, and electronic use in reporting activities system contributes to efforts to make difficult corruption. The corruption eradication in each country will apply differently according to the condition and resources available. Keywords: Corruption, Eradication, Asia Country Abstrak Penelitian ini membahas tentang upaya pemberantasan korupsi di negara Asia yang dimanifestasikan dari bentuk korupsi itu sendiri. Untuk tujuan itu, penelitian ini mengadopsi kajian pustaka untuk menelusuri cara pemberantasan korupsi (data sekunder). Sementara itu, dari penelusuran analisis kajian pustaka memberikan informasi bahwa pemberantasan korupsi lebih diarahkan kepada tindakan pencegahan melalui pendidikan korupsi tingkat usia dini pada program sekolah dasar sebagai investasi integritas masa depan. Partisipasi masyarakat, kerja sama berbagai institusi, tata kelola pemerintahan, dan penggunaan elektronik dalam aktivitas pelaporan berkontribusi dalam upaya mempersulit tindakan korupsi. Pemberantasan korupsi di setiap negara akan menerapkan cara yang berbeda sesuai dengan keadaan, dan sumber daya yang tersedia. Kata Kunci: Korupsi, Pemberantasan Korupsi, Negara Asia